Lipomatous Hypertrophy: An Accidental Finding in Heart - Petrelli, F. (Case Rep Pathol, 2019)
Lipomatous hypertrophy is an uncommon benign lesion of the atrium, generally asymptomatic, characterized by unencapsulated accumulation of adipose tissue entrapping cardiomyocytes. This pathology generally remains unnoticed and often emerges as an occasional finding. Here, we report two cases from our hospital including a review of the available literature.